Effect of Date of Planting and Seed Treatment to Control Late Blight (Phytophthora infestans) Disease of Potato in Nigale, Sindhupalchowk - Shrestha, Astha; Devkota, Durga; Senchuri, Apekshya; Adhikari, Gaurav (Nepalese Horticulture, 2024)
An experiment was conducted from February to June 2020 with the objective to analyse the effect of the date of planting and fungicidal seed treatment to control the late blight disease of potato in Sindhupalchowk district. The experiment was done in a split plot design and each treatment was replicated three times. The main-plot factor was the planting dates; February 15 and March 15 and the sub-plot factor was the seed treatments with fungicides application of (i) Bavistin @0.2% concentration, (ii) Mancozeb @0.25% concentration, (iii) Krilaxyl @0.2% concentration, and (iv) untreated control. Potato variety used was Kufri Jyoti, a released variety for the hills of Nepal. Records were maintained for major pathological parameters at different dates. The fungicidal seed treatment had a significant (p<0.05) effect on disease severity after the appearance of the disease, but was non-significant to disease incidence. Disease severity was the least on Mancozeb treatment (4), but was statistically similar to the other two treatments Bavistin (4) and Krilaxyl (5). The planting dates had a non-significant effect on disease severity but least disease severity was found with the application of Mancozeb planted on March 15 (3). Further validation of the results with in-depth study is required before coming to concrete findings.